International enterprise in Poland - benefits and risks = Przedsiębiorstwo międzynarodowe w Polsce - korzyści i zagrożenia - Glinkowska, Beata; Kaczmarek, Bogusław (Zielona Góra: Faculty of Economics and Management Press)
The article presents chosen issues of inflow of FDI to Poland. The essence and definition of international enterprise is explained as well as the FDI number in Poland in 2014. An increase trend of FDI in Poland is presented the basis of statistical data. An influence of FDI on Polish GDP in years 2000-2013 was analysed. The directions of FDI inflow in Poland in years 2008-2013 are compared. The focus was on benefits and risks related to the presence of foreign enterprises in Poland, allowing for achievement of the objective of this study.
Keywords: bezpośrednie inwestycje zagraniczne; BIZ; przedsiębiorstwo międzynarodowe; rynek macierzysty; rynek goszczący; internacjonalizacja; foreign direct investment; FDI; international enterprise; home market; host market; internationalization